Attitudes and achievement orientations of students towards learning of science and mathematics in English - Tan, Yao Sua (Universiti Sains Malaysia, 2007)
This study examines the policy of teaching science and mathematics in English in the Malaysian educational system by focusing on the attitudes and achievement orientations of secondary school students towards the learning of these two subjects. Attitudes and achievement are two important outcomes of learning that will determine the effectiveness of an education policy. This study is based on a sample of 400 secondary school students selected from four non-premier schools. It looks into the students’ general attitudes and achievement orientations towards learning of science and mathematics as well as their variations according to four background variables, i.e., gender, ethnicity, types of feeder school and English achievement grades. It also examines the inter-correlations between the students’ attitudes and achievement orientations. Findings from statistical analyses of collected data were supplemented by more in-depth interviews. This study shows that the students’ general attitudes and achievement orientations towards learning of science and mathematics in English do not indicate that the policy has achieved its objective. However, their attitudes and achievement motivations vary according to the four background variables. The significant and positive inter-correlations between attitudes and achievement orientations towards learning of science and mathematics further confirm the causal relationship between these two important dimensions of learning.